Genesis Institutionalism in the Works of Ukrainian Scientists XX–XXI Century (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The paper summarizes the domestic and foreign approaches to the concept of institution, and its value is determined in the current process of economic growth. Traced the evolution of institutionalism as the direction of modern economic science at the beginning of XXI century. Analyzes the activity of Ukrainian schools institutionalism. Structured stages of Ukrainian institutional direction, from its inception the twentieth century to the present. Enumerated representatives ofcorporate institutionalism movement in Ukraine, and emphasizes their impact on the Ukrainian economy a specific period.
Keywords: institutionalism, college, corporate movement neoinstytutsionalizm